Saklar Kontrol Hand Sanitizer Otomatis Menggunakan Jarak Pada Infrared Sensor Obstacle Avoidance - Rila Afhrila; Rahmat Hidayat (Jurnal Ilmiah Wahana Pendidikan, 2023)
During the COVID-19 pandemic, the use of hand sanitizers as a practical way to kill viruses has been widely adopted. Typically, hand sanitizers are manually used by spraying the liquid from a spray bottle onto the user's hands. The introduction of a simple innovation in hand sanitizers utilizing automatic control provides convenience to the public. This innovation involves the use of an infrared sensor to detect the user's hands as an object to activate the device. An IR Obstacle Avoidance sensor is used as the input for the automatic control of the hand sanitizer. An Arduino Uno R3 is used as the data processing microcontroller, along with a Micro Servo SG90 as the lever actuator. The operation and testing of this device involve bringing the user's hand close to the sensor located at the front of the bottle. When the sensor detects hand movement, it sends a command to pull the bottle's sanitizer dispenser lever, allowing the sanitizer to be dispensed automatically. An automatic hand sanitizer device with an infrared sensor can help reduce the risk of virus and bacteria transmission through surface contact, as users do not need to touch the device to dispense the sanitizer. This device can also be effectively used in public places such as offices, schools, restaurants, and others, to enhance safety and environmental cleanliness.sebagainya, untuk meningkatkan keamanan dan kebersihan lingkungan.